The psychology of technology: social science research in the age of big data - Matz, Sandra (American Psychological Association, 2022)
Machine generated contents note: Foreword: The Critical Role of Psychological Science in Understanding The Human-Technology Relationship -- Introduction: Welcome to the Psychology of Technology -- Chapter 1: What Our Data Reveal About Our Minds: Predicting Psychological Characteristics from Digital Footprints -- Chapter 2: Saying More Than We Know: How Language Provides a Window into the Human Psyche -- Chapter 3: The Big Data toolkit for Psychologists: Data Sources and Methodologies -- Chapter 4: The Psychology of Mobile Technology and Daily Mobility -- Chapter 5: "The Psychology of Virtual Reality" -- Chapter 6: Social Media and Psychological Well-Being -- Chapter 7: How social media contexts affect the expression of moral emotions -- Chapter 8: Big Data in The Workplace -- Chapter 9: Human-Robot Interaction Challenges in the Workplace -- Chapter 10: The Psychology of Big Data- Developing a "Theory of Machine" to Examine Perceptions of Algorithms -- Chapter 11: Privacy and Ethics in the Age of Big Data -- Chapter 12: The Psychology of Technology- Where the Future Might Take Us -- .